CURRENT AND VOLTAGE MONITORING SYSTEM BASED ON MEASUREMENTS ON SOLAR PANEL BASED ON ARDUINO UNO - Sadi, Sumardi; Mulyati, Sri; Putro, Fajar Miarso (Journal of Research in Construction, Communication, and Commercial, 2022)
The performance of solar panels can be directly monitored for parameters such as voltage and current. From the monitoring results, information can be obtained whether the installation of solar panels is as expected. However, in some existing studies there are still shortcomings, namely both current and voltage measurements are still carried out manually using a multimeter, so the data taken cannot be recorded continuously. Therefore, the purpose of this tool is to create a measurement monitoring system on the output of solar panels. At the time of measurement to detect current and voltage, a lot of measurement data is needed. Tools and materials used to obtain Solar Panel output data, this system uses two measurement sensors, namely the ACS712 current sensor as a current meter and a voltage sensor. These two measurement sensors will send the current and voltage values ​​to the Arduino Uno microcontroller. The microcontroller will give a command to the stepper motor to move the rheostat wiper so that the resistance on the rheostat will change. Any data that is read by the microcontroller will be continuously sent to the flash that has been installed. The method used is by testing the tool by measuring the output on the solar panel. The results of the measurement of the system as a whole show that the difference between the sensor and the multimeter is 0.126 V for the voltage value and 0.018 A for the current value. The microcontroller will give a command to the stepper motor to move the rheostat wiper so that the resistance on the rheostat will change. Any data that is read by the microcontroller will be continuously sent to the flash that has been installed. The method used is by testing the tool by measuring the output on the solar panel. The results of the measurement of the system as a whole show that the difference between the sensor and the multimeter is 0.126 V for the voltage value and 0.018 A for the current value. The microcontroller will give a command to the stepper motor to move the rheostat wiper so that the resistance on the rheostat will change. Any data that is read by the microcontroller will be continuously sent to the flash that has been installed. The method used is by testing the tool by measuring the output on the solar panel. The results of the measurement of the system as a whole show that the difference between the sensor and the multimeter is 0.126 V for the voltage value and 0.018 A for the current value.